2019
DOI: 10.3389/fnmol.2019.00027
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress Delays Sexual Maturation in Female Mice

Abstract: In humans, some forms of early life stress (ELS) have been linked with precocious puberty, altered brain maturation, and increased risk for a variety of forms of pathology. Interestingly, not all forms of ELS have been found to equally impact these metrics of maturation. In recent work, we have found that ELS in the form of limited bedding (LB) from P4 to P11, was associated with precocious hippocampus maturation in males and increased risk for depressive-like pathology and attentional disturbance in female mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 72 publications
2
30
2
Order By: Relevance
“…Previous research from our group and others have found effects of LB on depressive-like behavior in females ( Goodwill et al, 2019 ), but failed to find significant differences in anxiety-like behavior in adult mice ( Goodwill et al, 2019 ; Manzano Nieves et al, 2019 ; Manzano-Nieves et al, 2018 ; Naninck et al, 2015 ). Consistent with previous work, we did not find an effect of LB on general measures of anxiety.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Previous research from our group and others have found effects of LB on depressive-like behavior in females ( Goodwill et al, 2019 ), but failed to find significant differences in anxiety-like behavior in adult mice ( Goodwill et al, 2019 ; Manzano Nieves et al, 2019 ; Manzano-Nieves et al, 2018 ; Naninck et al, 2015 ). Consistent with previous work, we did not find an effect of LB on general measures of anxiety.…”
Section: Discussioncontrasting
confidence: 68%
“…To assess anxiety-like behavior at PND 21 mice were placed in an elevated plus maze as previously described ( Manzano Nieves et al, 2019 ; Manzano-Nieves et al, 2018 ). The EPM consisted of two open (unprotected) and two closed (protected) arms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal differences in body weight at puberty onset suggest that, irrespective of early life background and subsequent body weight at weaning, the majority of mice postpone the onset of puberty until a certain body weight is reached. This is in contrast to a recent study where body weight at vaginal opening was increased in female mice that were reared in a LN condition from P2‐9 28 . However, because body weight at weaning of control groups is similar in both studies, this is unlikely to be a result of measurement differences.…”
Section: Discussioncontrasting
confidence: 97%
“…In line with a previous study, 18 we focused on timing of puberty onset, a key moment in development that is malleable by environmental influences as part of an adaptive reproductive strategy 25 . Although adverse rearing conditions in females are linked to accelerated pubertal onset in humans 26 and rats, 27 such effects have not yet been observed in mice 18,28 . In human males, adverse rearing conditions had no effect on puberty onset, 29 while puberty onset in male rodents was either unaffected or delayed 18,27,30 .…”
Section: Introductionmentioning
confidence: 73%